2022
DOI: 10.1002/jsfa.12092
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental and sensory analyses of fruit quality attributes of grafted grape tomatoes in high tunnel organic production systems

Abstract: BACKGROUND: 'Vegetative' and 'generative' tomato rootstock types have been proposed based on their different effects on tomato scion growth performance; however, their impacts on fruit quality have not been characterized. No study has been conducted in which the effects of rootstock on grape tomato quality attributes were assessed using sensory and instrumental methods of evaluation. Here, we conducted two experiments to examine the influence of 'DR0141TX', 'Estamino', and 'Multifort' rootstocks (vegetative, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Notably, the TA was lower in fruits on grafted vines, while no significant difference was detected in SSC. Similar results were reported by Gong et al [73].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the TA was lower in fruits on grafted vines, while no significant difference was detected in SSC. Similar results were reported by Gong et al [73].…”
Section: Discussionsupporting
confidence: 92%
“… Lang et al (2020) also evaluated the same three rootstocks (‘DR0141TX’, ‘Estamino’, and ‘RST-04-106-T’) in a 2-year high tunnel study and found that they did not impact beefsteak tomato firmness, which was in agreement with our findings in Fall planting. Our previous study involving both ‘DR0141TX’ and ‘Estamino’ showed that the impacts of these two rootstocks on grape tomato firmness varied with harvest dates ( Gong et al, 2022 ). In terms of effects of rootstock genetic background on tomato fruit firmness, we found that interspecific rootstock ‘Estamino’ consistently decreased fruit firmness of beefsteak tomato but not grape tomato in both planting seasons, while the intraspecific rootstock ‘Shield’ showed no impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently lower tomato fruit dry matter content with grafting onto interspecific rootstocks (‘Estamino’) in the present study was also observed by Turhan et al (2011) and Djidonou et al (2016) . Moreover, our previous studies involving three vigorous rootstocks (‘DR0141TX’, ‘Estamino’, and ‘Multifort’) showed that rootstock impacts on fruit dry matter content of grape tomato fruit varied with harvest dates and scion cultivars ( Gong et al, 2022 ). In contrast, Gioia et al (2010) demonstrated that interspecific rootstocks ( S. lycopersicum × S. habrochaites ) did not affect fruit dry matter content regardless of harvest dates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations